Dose-dependent hepatotoxicity of liraglutide in pregnant wistar rats (Research, Society and Development, 2025)
The aim of this study was to evaluate the possible hepatotoxic effects of liraglutide, a GLP-1 analog used in the treatment of obesity and type 2 diabetes. Twenty Wistar rats (Rattus norvegicus) were used, divided into four groups (control, 0.007 mg/mL, 0.07 mg/mL and 0.7 mg/mL) and treated for 21 days (gestation). The study was submitted to and approved by CEUA/UNIPAM under protocol number 94/23. After inhalation anesthesia with isofluorane, laparatomy was performed followed by blood collection for biochemical tests, euthanasia and removal of the livers for weighing and histopathological analysis. There were no statistically significant changes (p>0.05) in the levels of the liver enzymes ALT and AST, despite the high variation in the standard deviation observed in some groups (0.07mg/mL and 0.7mg/mL) according to the ANOVA/Tukey statistical test. There was a significant reduction (p0.05) between the groups according to the Kruskal-Wallis statistical test, followed by Dunn's method. It is concluded that liraglutide, even at high doses, did not demonstrate significant hepatotoxicity in pregnant rats. However, further studies with larger sample sizes and molecular investigations are recommended to confirm the safety of liraglutide use during pregnancy.